Growth and Development of Air and Space Law - Abdurrasyid, Priyatna (Indonesian Journal of International Law, 2021)
The article provides a brief background on the development of air and space law from the historical perspective. It concludes that the scientific discipline of air law can be dissected from several elements, namely geographical elements, temporal elements, personal elements, material elements, and functional elements. With regard to space law, the article provides its scientific development and its ramification to other disciplines, most importantly telecommunication law.